Competition with insectivorous ants as a contributor to low songbird diversity at low elevations in the eastern Himalaya. Issue 10 (30th March 2020) - Supriya, K.; Price, Trevor D.; Moreau, Corrie S.
Abstract: Competitive interactions between distantly related clades could cause complementary diversity patterns of these clades over large spatial scales. One such example might be ants and birds in the eastern Himalaya; ants are very common at low elevations but almost absent at mid‐elevations where the abundance of other arthropods and insectivorous bird diversity peaks. Here, we ask if ants at low elevations could compete with birds for arthropod prey. Specifically, we studied the impact of the Asian weaver ant ( Oecophylla smaragdina ), a common aggressive ant at low elevations. Diet analysis using molecular methods demonstrate extensive diet overlap between weaver ants and songbirds at both low and mid‐elevations. Trees without weaver ants have greater non‐ant arthropod abundance and leaf damage. Experimental removal of weaver ants results in an increase in the abundance of non‐ant arthropods. Notably, numbers of Coleoptera and Lepidoptera were most affected by removal experiments and were prominent components of both bird and weaver ant diets. Our results suggest that songbirds and weaver ants might potentially compete with each other for arthropod prey at low elevations, thereby contributing to lower insectivorous bird diversity at low elevations in eastern Himalaya. Competition with ants may shape vertebrate diversity patterns across broad biodiversity gradients. Abstract : Competitive interactions between distantly related clades could cause complementary diversity patterns of these clades over large spatial scales. One such example might be ants and birds in the eastern Himalaya; ants are very common at low elevations but almost absent at mid‐elevations where the abundance of other arthropods and insectivorous bird diversity peaks. Here, we present some evidence for dietary overlap between Asian Weaver ants and birds at low elevations and show that removal of weaver ants results in increase in non‐ant arthropod population on trees.